Autonomous Vehicle Data Protection : A Review of Security Threats, Challenges and Protective Mechanism - Gowthami M; Dr. Gowthami V (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The swift advancement of autonomous vehicle (AV) technology has presented notable obstacles with data security and privacy. This analysis examines major security threats that jeopardize user privacy and vehicle control, including data breaches, virus penetration, cyber attacks, illegal access, V2V and V2I system hacking, GPS spoofing, and data leaks. It also looks at the challenges developers have when putting strong security measures in place, considering how complicated AV infrastructures may be and how cloud, IoT, and AI are integrated. The paper outlines a number of defence tactics, such as blockchain technology, machine learning for anomaly detection, encryption, and secure communication protocols. In order to improve AV cyber security, it ends with suggestions for further study in fields like edge computing and quantum-resistant cryptography.